SOSIALISASI SISTEM PENDATAAN KEBUDAYAAN TERPADU DALAM MEWUJUDKAN PERLINDUNGAN HUKUM KARYA BUDAYA - Jayantiari, I.G.A.M.R.; Aryani, N.M.; Purwani, S.P.; Sari, C.I.I.S. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i05.p06, 2023)
This service aims to promote an integrated cultural data collection system that integrates all cultural data from various sources. The idealization of the state regime in providing legal protection for various cultural works of the community is realized through Law Number 5 of 2017 concerning the Advancement of Culture which is contained in Government Regulation Number 8 of 2021. Craftsmen of carving typical of Guwang Village, Sukawati District, Gianyar Regency are the target of this service . This is because the cultural works produced by the local community contain priceless unique art, so that their protection is optimized. In addition, material and immaterial benefits which, if carefully calculated, are a source of livelihood and the realization of welfare for the community. The service method is carried out through discussions, lectures, and questions and answers as well as reviewing actions in collecting carving data as an individual or communal identity in Guwang Village, Sukawati District, Gianyar Regency. The service activities went well and were welcomed interactively which fostered mutual awareness that an integrated cultural data collection system required the participation of all cultural owners. Keywords: Objects of Cultural Advancement, Legal Protection, Socialization.